THE UTILIZATION OF GRAMMAR SMASH TO IMPROVE THE ENGLISH GRAMMAR OF THE TENTH GRADE STUDENTS OF SMA JAYA NEGARA MAKASSAR - Istiana Wayan Bindau; Sulviana S; Jusmaniar N (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
This study aims to examine the effectiveness of using Grammar Smash application in improving students’ English grammar, especially on Simple Present Tense material, at class X students of SMA Jaya Negara Makassar. The research method used is Quasi-Experimental design with Non-equivalent Control Group design, which involves two groups, namely the experimental group using Grammar Smash application and the control group using conventional learning method. The research sample consisted of 20 students divided into two groups, 10 students each for the experimental group and 10 students for the control group. Data was collected through Pre-test and Post-test to measure the improvement of students' English grammar skills before and after the use of the application. the application. The results showed that the use of Grammar Smash application significantly improved students' English grammar, especially on Simple Present Tense material. This can be seen from the increase in the average post-test score in the experimental group from 41.50 to 88.50, while in the control group the increase in the average score was only from 31.00 to 67.00. Statistical analysis using Paired Sample t-test showed that the difference in score improvement between the Experimental and Control Groups was statistically significant (p < 0.05). After checking the hypothesis, the result shows t-obtained 4.386 is higher than t-table value 2.145. It can be concluded that (Ho) is rejected and (Ha) is accepted, so the results are considered significant using Grammar Smash application in learning Grammar especially in the aspect of Simple Present Tense in students. In addition, observation during the learning process shows that students are more motivated and actively involved in learning when using Grammar Smash application.